Concentrations of indomethacin and its metabolite desmethylindomethacin in plasma and urine after repeated indomethacin topical application to Thoroughbreds. (19th December 2018) - Kusano, K.; Minamijima, Y.; Mashita, S.; Kunii, H.; Yamashita, S.; Nagata, S.
Summary: Background: Repeated topical application of indomethacin is common in Japanese racehorses, despite the lack of pharmacokinetic data. Objectives: To determine the concentrations of indomethacin and its metabolite, desmethylindomethacin, in plasma and urine of Thoroughbreds topically treated repeatedly with indomethacin. Study design: In vivo experimental. Methods: Seven female Thoroughbreds were topically treated with 50 g of 1% indomethacin cream per horse to the back and hips (500 mg of indomethacin/head/2400 cm 2, 0.21 g/cm 2 ) for 3 consecutive days. Samples were pretreated by protein precipitation for plasma and liquid‐liquid extraction with ethyl acetate after hydrolysis with hydrochloric acid for urine. The concentrations of indomethacin and desmethylindomethacin in plasma and urine were measured by liquid chromatography‐mass spectrometry. Results: Indomethacin was quantifiable in plasma up to 48–72 h and in urine up to 96 h after the final application. Desmethylindomethacin was quantifiable in plasma up to 48 h and in urine up to 72–96 h after the final application. Main limitations: The relationship between the local and systemic indomethacin concentrations after the topical application was not clarified. Conclusions: Pharmacokinetic data were acquired for repeated topical administration of 1% indomethacin cream to Thoroughbreds. Hydrolysing urine samples with hydrochloric acid was effective for the analysis of indomethacin and its metabolite, and indomethacin may be an excellent marker analyte for doping tests. The estimated withdrawal time based on the limit of detection was 342 h.